Felt as an unsolved code of the past – a bridge to the future - Тентиева, Ч.Ж. (Искусство Евразии, 2017)
В статье рассмотрены вопросы истории развития художественной обработки войлока в Кыргызстане на примере работ из коллекции Кыргызского национального музея изобразительного искусства им. Г. Айтиева. Акцентируется внимание на творчество Джумабая Уметова, который возродил древнейшее ремесло среднеазиатских народов войлока и чия как новой области декоративно-монументального искусства. Продолжая традиции Уметова, работают на качественно новом уровне такие мастера, как Токтогул Касымов, Райгуль Акматова, Галина Турдиева. Современное декоративное искусство выросло на основе народного творчества. Сохраняя традиции, художники Кыргызстана развивают декоративно-прикладное искусство, внося новые темы, решения, осваивая новые виды, материалы и техники, формируя облик нового интерьера. The article discusses the history of felting in Kyrgyzstan based on the works from the collection of Kyrgyz National Museum of Fine Arts by G. Aytiev. The special attention is paid to works made by Jumabai Umetov , who revived the ancient craft of the Central Asian peoples connected with  felt and cane as a new field of decorative and monumental art. Continuing Umetov's traditions such high-level masters as Toktogul Kasymov, Raigul Akmatova, Galina Turdieva work at a qualitatively new level. Modern arts and crafts art grew up from the folk art. Keeping traditions, introducing new themes, solutions, mastering new materials and techniques, forming the new appearance of interior the artists of Kyrgyzstan develop arts and crafts.